Associação de polimorfismos em genes de citocinas e o desenvolvimento de inibidores na hemofilia A - Alencar, Josiane Bazzo de (2013)
Hemophilia A (HA) is a hereditary recessive disease X-linked caused by a deficiency of factor VIII (FVIII) blood clotting. It is estimated that there are approximately 10,065 patients with HA in Brazil. The basis of treatment of HA is the administration of concentrate of FVIII plasma-derived or recombinant product. Some patients develop antibodies that neutralize the activity of FVIII infused, defined as FVIII inhibitors, thus reducing the treatment efficiency and compromising hemostasis. Several factors may have the potential to influence this process, including immune response genes. Polymorphisms in regulatory regions of cytokine genes are being studied in association with risk of development of inhibitors in patients with HA. Studies have shown that the main polymorphisms associated with an increased risk of developing inhibitors are in the genes IL10 and TNF. The identification of these genetic factors, in particular cytokine genes, involved in the production of inhibitors by hemophiliacs patients may assist in preventing the inhibitory effect of FVIII. Therefore, this study analyzed the polymorphisms in regulatory regions of cytokine genes that could be associated with the risk of inhibitors development in patients with HA in the State of Paraná. The HA patients registered in Hemovidaweb-Coagulopathies in Paraná were selected to the study. Cytokine genotyping was performed by PCR-SSP kit cytokines using the Invitrogen®. The results indicated increased susceptibility to inhibitors development in patients with the +874T allele and +874TT genotype in gene INFG; and +869TT genotype in TGF-1. However, patients with the +874A allele of the gene INFG; the allele +1902A in IL4RA; and CG haplotype in the TGFB1 are lower risk to develop inhibitors. This study assists to identify promising genes to clinical practice, as well as contributing to trace a genetic profile of patients HA severely affected.